2022
DOI: 10.3390/cancers14215380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Phenotypic Markers and Outcomes of Diffuse Large B-Cell Lymphoma between HIV-Infected and HIV-Uninfected Chinese Patients

Abstract: Background: The effect of HIV infection on the clinicopathological characteristics of diffuse large B-cell lymphoma (DLBCL) remains debatable. Methods: Fifty-three HIV-infected and ninety-three HIV-uninfected DLBCL patients were enrolled in the retrospective study by propensity score matching for sex, age, body mass index and international prognostic index (IPI) at a ratio of 1:2. The clinicopathological characteristics were compared between the two groups. Results: HIV-infected DLBCL patients had lower white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that persistent in ammation and malnutrition are both associated with unfavorable outcomes in patients with HIV-related DLBCL [13][14][15] . Given that CHE is an important indicator of chronic in ammation and malnutrition, we hypothesize that serum CHE levels may be associated with the progression and prognosis of HIV-related DLBCL.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that persistent in ammation and malnutrition are both associated with unfavorable outcomes in patients with HIV-related DLBCL [13][14][15] . Given that CHE is an important indicator of chronic in ammation and malnutrition, we hypothesize that serum CHE levels may be associated with the progression and prognosis of HIV-related DLBCL.…”
Section: Introductionmentioning
confidence: 97%
“…Zhou et al explore the clinical features, phenotypic markers, and outcomes of diffuse large B-cell lymphoma (DLBCL) in HIV-infected and HIV-uninfected Chinese patients. The results indicate that HIV-infected DLBCL patients exhibit distinct blood and phenotypic markers, with lower response rates and one-year survival rates, likely due to increased hematological complications and widespread organ involvement [6]. Also, another study in this Special Issue suggests that TFF1 and TFF2 may function as potential tumor suppressors in Gastric cancer (GC), offering valuable insights for predicting overall survival (OS) in GC patients.…”
mentioning
confidence: 98%